2018
DOI: 10.3390/ijms20010103
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminases Post-Translationally Deiminate Prohibitin and Modulate Extracellular Vesicle Release and MicroRNAs in Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most aggressive form of adult primary malignant brain tumour with poor prognosis. Extracellular vesicles (EVs) are a key-mediator through which GBM cells promote a pro-oncogenic microenvironment. Peptidylarginine deiminases (PADs), which catalyze the post-translational protein deimination of target proteins, are implicated in cancer, including via EV modulation. Pan-PAD inhibitor Cl-amidine affected EV release from GBM cells, and EV related microRNA cargo, with reduced pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
121
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(128 citation statements)
references
References 122 publications
6
121
0
Order By: Relevance
“…PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019). While studies on PADs in relation to human pathophysiology, including cancer, autoimmune and neurodegenerative diseases (Wang and Wang, 2013;Witalison et al, 2015;Lange et al, 2017;Kosgodage et al, 2017Kosgodage et al, & 2018 and CNS regeneration (Lange et al, 2011 and2014) exist, relatively little phylogenetic research has been carried out on PADs in relation to normal physiology and evolutionary acquired adaptions of the immune system. Recent comparative studies focussing on roles for PADs in teleost fish have identified post-translational deimination in key proteins of innate, adaptive and mucosal immunity (Magnadóttir et al, 2018a, b;Magnadottir et al, 2019a;Magnadóttir et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019). While studies on PADs in relation to human pathophysiology, including cancer, autoimmune and neurodegenerative diseases (Wang and Wang, 2013;Witalison et al, 2015;Lange et al, 2017;Kosgodage et al, 2017Kosgodage et al, & 2018 and CNS regeneration (Lange et al, 2011 and2014) exist, relatively little phylogenetic research has been carried out on PADs in relation to normal physiology and evolutionary acquired adaptions of the immune system. Recent comparative studies focussing on roles for PADs in teleost fish have identified post-translational deimination in key proteins of innate, adaptive and mucosal immunity (Magnadóttir et al, 2018a, b;Magnadottir et al, 2019a;Magnadóttir et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…As PADs have been identified to be a key regulator of extracellular (EV)-release, a mechanism that has been found to be phylogenetically conserved from bacteria to mammals (Kholia et al, 2015;Kosgodage et al, 2017Kosgodage et al, , 2018Gavinho et al, 2019;Kosgodage et al, 2019), the characterisation of EVs in camelids is of further interest. Extracellular vesicles (EVs) are found in most body fluids and participate in cellular communication via transfer of cargo proteins and genetic material (Inal et al, 2013;Colombo et al, 2014;Lange et al, 2017;Turchinovich et al, 2019;Vagner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that EVs are released by multiple mechanisms, some advances in understanding of their biogenesis has been elucidated via studies on the peptidylarginine deiminase (PAD)-mediated pathway of EV release (Kholia et al, 2015; Kosgodage et al, 2017; Lange et al, 2017; Kosgodage et al, 2018a). PADs are phylogenetically conserved enzymes from bacteria to mammals (Vossenaar et al, 2003; Magnadottir et al, 2018), including in Giardia (arginine deiminase GiADI; Trejo-Soto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While exact roles for PADs in EV biogenesis and release remain to be fully elucidated, effects on cytoskeletal, nuclear and mitochondrial proteins have been reported (Kholia et al, 2015; Kosgodage et al, 2018). As pharmacological PAD-inhibitors have previously been shown to be potent inhibitors of EV release in various cancer cells, as well as to modulate EV cargo (Kholia et al, 2015; Kosgodage et al, 2017; Kosgodage et al, 2018a), we sought to investigate a phylogenetically conserved influence of such PAD-inhibitors on the EV production of our protozoa model; putatively targeting GiADI and therefore also reveal a role for GiADI in EV release.…”
Section: Introductionmentioning
confidence: 99%